Biomass Evolution in Full‐Scale Anthracite‐Sand Drinking Water Filters Following Conversion to Biofiltration. Issue 12 (1st December 2016) - Stoddart, Amina K.; Schmidt, Jordan J.; Gagnon, Graham A.
Abstract : This study investigated biomass concentrations, as measured by adenosine triphosphate (ATP), in full‐scale, anthracite–sand biofilters as they acclimated to conversion from direct filtration to biofiltration. Results showed that there were three scales of biofilter biomass accumulation: an accumulation period within each filter cycle, and an accumulation period associated with adapting to chlorine‐free conditions for both biomass measured at the start and end of the filter cycle. Both start‐ and end‐of‐cycle biomass reached steady state after 220 days of operation. Start‐of‐filter‐cycle biomass accumulated at a rate of 0.008/day and reached a steady‐state concentration of 59 ng ATP/cm 3 media. End‐of‐filter‐cycle biomass reached an apparent steady‐state concentration of 267 ng ATP/cm 3 media. Biomass measured over a single filter cycle had an accumulation pattern similar to start‐of‐filter‐cycle biomass but accumulated more rapidly (1.96–4.46/day).